AB0835 Comparison of long term anti-tnf survival in patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis; data from turkbio registry. (12th June 2018) - Can, G.; Dalkilic, E.; Pehlivan, Y.; Senel, S.; Akar, S.; Solmaz, D.; Koca, S.S.; Inanc, N.; Atagunduz, P.; Yazıcı, A.; Cefle, A.; Goker, B.; et al.
Abstract : Background: Limited data are available on anti-TNF survival in non-radiographic axial spondyloarthritis (nr-axSpA) patients and their long-term survival in ankylosing spondylitis (AS). Objectives: The aim of the study was to evaluate long term survival of the first anti-TNF drug treatment among patients with AS and nr-axSpA enrolled in the TURKBIO database and to compare the discontinuation rates for infliximab (INF), etanercept (ETN), and adalimumab (ADA) in each of the two groups. Methods: All AS and nr-axSpA patients receiving biological therapies registered in the TURKBIO database between the dates of october 2011 and april 2017 were included in the study. AS diagnosis was made according to modified New York classification criteria and nr-axSpA according to ASAS AxSpA classification criteria. Demographic and clinical data, the date of starting to use biological drug, using frequency and dose of biological drugs, BASFI, BASDAI, BASMI, ASDAS scores, date and reason for discontinuing to use drug were collected. Baseline characteristics and drug survival rates were compared between AS and nr-axSpA patients. Drug survival was calculated by the Kaplan-Meier method and risk for discontinuation among treatment groups cpmpared by Long Rank test. Results: A total of 924 patients were included in the study (AS, n=871 and nr-axSpA, n=53). More than half of the patients with AS were male (60.7% in AS vs 34.0% in nr-axSpA group, p<0.001).AS patients had longer symptom duration (104.90±79.06 vs 75.11±45.29 months, p<0.036) compared to nr-axSpA. Median levels of CRP and ESR were similar for nr-axSpA (CRP: 27.03±34.71, ESR: 30.50±25.77) and AS (CRP: 22.32±29.95, ESR: 35.40±22.91). The scores of BASFI, BASMI and ASDAS were found to be similar in both groups. Median BASDAI scores at first TNFi initiation were higher in patients with nr-axSpA than in patients with AS (58.65±18.21, 51.06±18.91, p=0.030). Cumulative drug survival rates did not show significant difference among INF (at 59. months:18, 5%), ADA (at 71. months: 39, 5%) and ETN (at 51. months: 24, 2%) in nr-axSpA group (p=0, 699) (figure 1). Similarly, drug survival rates at 78, 77, 78. months for 3 anti-TNF drugs had shown no difference in AS patients (INF (at 78. months: 38, 1%), ADA (at 77. months: 52, 4%), ETN (at 78. months: 39, 0%)) (p=0, 151) (Figure 2). Cumulative survival rates in AS patients (at 78. months:42, 2%) were found to be significantly higher than that (at 71. months:28, 2%) in nr-axSpA patients (p<0, 001) (Figure 3). Conclusions: In contrast to the literature that revealed similar short term survival rates for anti-TNF drugs in patients with AS and nr-axSPA, we found higher survival rates in patients with AS compared to patients with nr-axSpa in this long-term observational study.A limitation of the study may be the low number of nr-axSpa patients using anti-TNF, related to the requirements of social insurance system. Disclosure of Interest: None declared